Acute Effect of Oral Administration of Fructose on Blood Parameters and Hepatic Glycogen in Layer Chicks - Komaki, Yoshinori; Fukano, Natsuki; Bungo , Takashi (International Journal of Poultry Science, 2017)
Objective: The aim of the present study was to investigate the effect of oral administration of fructose on blood parameters and hepatic glycogen in chickens. Materials and Methods: Each chick was injected orally once only with fructose solution (80 mg/0.2 mL) after 12 h fasting. The levels of plasma glucose and Free Fatty Acid (FFA) and hepatic glycogen were measured at 1, 2 or 3 h after administration and compared with levels in 12 h fasted and ad libitum chicks. Results: Although no significant differences were detected in blood parameters between the ad libitum and fasting condition, the level of hepatic glycogen in the fasted chicks was lower than that in the ad libitum chicks (p<0.05). The plasma glucose level at 2 h was significantly lower than that at 1 h post-injection (p<0.05). The concentration of FFA at 1 h post-injection was significantly lower than that in the fasted chicks (p<0.05). Conclusion: These results suggest that the administration of fructose affects carbohydrate and lipid metabolism in chicks.